A 71‐year‐old female with giant goiter associated with tracheomalacia. Issue 4 (26th June 2014) - Azuma, Kazunari; Oda, Jun; Oda, Kaori; Homma, Hiroshi; Azuma, Hikohiro; Uchida, Kotaro; Matsuoka, Yuji; Kobayashi, Tomoko; Yukioka, Tetsuo
<x xml:space="preserve">Abstract</x> Case A 71‐year‐old woman was admitted to the Emergency Department with severe dyspnea followed by unconsciousness. She had a history of hyperthyroidism and her anterior neck was markedly swollen. After ventilation was started, she soon became conscious with the improvement of oxygenation. Computed tomography findings indicated giant goiter surrounding the trachea. Later, we carried out a thyroidectomy for the giant goiter (800 g), and tracheostomy. Bronchoscopy carried out at the end of surgery showed a deformed tracheal wall on breathing. During inspiration, the collapsed wall of the trachea occluded the airway, although the tracheal wall recovered to normal during expiration. We diagnosed this case as acquired tracheomalacia and a tracheal stent graft made of silicon was inserted immediately after bronchoscopy. Outcome After stent graft insertion, the patient was transferred to another hospital. Conclusion Emergency physicians should be aware of the causes of tracheomalacia in order to safely carry out treatment, particularly in the case of patients with giant goiter.